Inspiracje filmowe w literaturze polskiej dwudziestolecia międzywojennego = Film inspirations in Polish literature of the interwar period - Otto, Wojciech (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The relationships between film and literature in Polish culture of the interwar period constitute an important element of socio-cultural transformations that occurred at that time in Poland and previously in Europe. For literature, film served as a catalyst of aesthetic changes on various levels: fictional, narrative and genealogic.
Keywords: film inspirations; Polish literature; interwar period; inspiracje filmowe; literatura polska; dwudziestolecie międzywojenne